Analysis of IPO Performance in Indonesia in the "Hot Market" Period and Its Influencing Factors - Agustina, Lidya -; Meyliana, Meyliana -; Joni, Joni - (Jurnal ASET (Akuntansi Riset), 2021)
The aim of this study is to test whether there is an underpricing phenomenon within the Hot Market period in Indonesian public companies in 2018. Among 56 companies which conducted IPOs, our descriptive statistical analysis shows 53 companies experienced underpricing and the rest experienced overpricing. We used nonparametric statistic to calculate the average of initial return, and multiple linear regression to test the effect of independent variables on the initial return. The result shows that the underpricing phenomenon occurred in IPO performance in Indonesia. Meanwhile, the results of hypothesis testing show that the company’s age and the underwriter’s reputation had no effect on initial return, while company’s size and market sentiment show a significant negative effect on initial return.